THOMAS BERTIE, THE MASTER-MASON AT WINCHESTER CATHEDRAL c 1515–50. (18th August 2015) - Riall, Nicholas
Abstract : This paper takes as its start-point the entry for Thomas Bertie in John Harvey's English Medieval Architects and uses it to explore the life and work of a master-mason who was trained in the Gothic tradition, but came to be one of the first to utilise Renaissance detail in his works in Winchester Cathedral and across Hampshire. Bertie's work encompassed an astonishing range of projects, extending from the remodelling of the presbytery of Winchester Cathedral to the construction of chapels and tomb monuments, and from the conversion of monastic buildings into country houses to helping create a chain of artillery forts to defend the south coast. The distinctive Renaissance style that appears on so many of these works allows a connection to be made between them and Thomas Bertie. RÉSUMÉ: Cet article, qui prend pour point de départ l'entrée consacrée par John Harvey à Thomas Bertie dans son ouvrage intitulé English Medieval Architects, explore la vie et l'œuvre de ce maître maçon de formation gothique, mais qui devint l'un des premiers à employer des détails de style renaissance dans les travaux qu'il mena à la cathédrale de Winchester et dans le Hampshire. L'œuvre de Bertie englobe un éventail étonnant de projets qui s'étend du remodelage du presbytère de la cathédrale de Winchester à la construction de chapelles et de monuments funéraires, et de la transformation de bâtiments monastiques en manoirs à une contribution à la création d'une série de forts d'artillerie destinée à défendre la côte sud. Le style renaissance distinctif observé dans nombre de ces ouvrages permet de les relier à Thomas Bertie. ZUSAMMENFASSUNG: Diese Abhandlung nimmt als ihren Ausgangspunkt einen Eintrag zu Thomas Bertie in John Harveys English Medieval Architects und verwendet ihn zur Erforschung von Leben und Werk eines Baumeisters, der in der gotischen Tradition ausgebildet worden war, dann aber als einer der Ersten Renaissanceelemente in seinen Werken in der Kathedrale von Winchester und in ganz Hampshire verwendet hat. Berties Tätigkeit umfasste eine erstaunliche Reihe von Projekten, von der Umgestaltung des Altarraums in der Kathedrale von Winchester bis hin zum Bau von Kapellen und Grabmälern, und von der Umwandlung klösterlicher Gebäude in Landsitze bis zur Errichtung einer Reihe von Geschützbefestigungen zur Verteidigung der englischen Südküste. Anhand des charakteristischen Renaissancestils, der an so vielen dieser Arbeiten zu erkennen ist, lässt sich eine Verbindung zwischen diesen Werken und Thomas Bertie herstellen.